The response and recovery of the Arabidopsis thaliana transcriptome to phosphate starvation - Woo, Jongchan (BioMed Central, 2012)
BACKGROUND: Over application of phosphate fertilizers in modern agriculture contaminates waterways and disrupts natural ecosystems. Nevertheless, this is a common practice among farmers, especially in developing countries as abundant fertilizers are believed to boost crop yields. The study of plant phosphate metabolism and its underlying genetic pathways is key to discovering methods of efficient fertilizer usage. The work presented here describes a genome-wide resource on the molecular dynamics underpinning the response and recovery in roots and shoots of Arabidopsis thaliana to phosphate-starvation. RESULTS: Genome-wide profiling by micro- and tiling-arrays (accessible from GEO: GSE34004) revealed minimal overlap between root and shoot transcriptomes suggesting two independent phosphate-starvation regulons. Novel gene expression patterns were detected for over 1000 candidates and were classified as either initial, persistent, or latent responders. Comparative analysis to AtGenExpress identified cohorts of genes co-regulated across multiple stimuli. The hormone ABA displayed a dominant role in regulating many phosphate-responsive candidates. Analysis of co-regulation enabled the determination of specific versus generic members of closely related gene families with respect to phosphate-starvation. Thus, among others, we showed that PHR1-regulated members of closely related phosphate-responsive families (PHT1;1, PHT1;7–9, SPX1-3, and PHO1;H1) display greater specificity to phosphate-starvation than their more generic counterparts. CONCLUSION: Our results uncover much larger, staged responses to phosphate-starvation than previously described. To our knowledge, this work describes the most complete genome-wide data on plant nutrient stress to-date.